Constructing the "Other": Discursive Mechanisms at Play in the Sentencing of Post 9/11 Canadian Terrorism Cases - MacLennan, Kirsten (Université d'Ottawa / University of Ottawa, 2020)
Since the renowned terrorist attacks of September 11th, 2001, exclusionary narratives or “othering” have proliferated in the securitized West. Prominently associated with media campaigns, popular culture, or political debates, exclusionary discourses operating within the Canadian judiciary have been largely overlooked. Inspired by the work of Giorgio Agamben and Richard Ericson, this study is a critical discourse analysis of sentencing decisions within five terrorism cases. Findings suggest that “othering” operates in these decisions through seven discursive mechanisms. Those mechanisms construct the offenders as Muslim non-conforming foreign “others” threatening the Canadian nation, and worthy of exclusion. As such, the offenders are seen as deserving of punitive incarceration by the severest extent of the law. The courts also justify this punishment by invoking political imperatives namely the need for the State to preserve its alliance with other nations engaged in the “War on Terrorism” and the necessity to counter the “discontent with the West”. Although limited by legal safeguards, the exceptional state power at play in the post 9/11 era is not without effect on the wider population of Muslim in Canada and abroad.
Keywords: Terrorism; Sentencing; Race; Canadian Judiciary